(untitled) (Bangladesh Journal of Medicine, 2018)
Background: In Bangladesh prevalence of malignancy in diabetic patients seems to be increasing as case detection of both diseases are far more than before. No statistical data of diabetic patients with malignancy is currently available in Bangladesh. Treatment of both diabetes and malignancy in the same patient is challenging for the physician and requires multidisciplinary support. For such cases BIRDEM General Hospital offers supportive facilities including intensive care, chemotherapy, surgical intervention and oncology day care. Methods : This is a cross-sectional observational study carried out from January 2011 to June 2016 which included adult diabetic patients with malignancy admitted in Internal Medicine Department of BIRDEM General Hospital. With prior informed consent of the patients, data were collected and statistical analysis was done using professional SPSS version 17.0 windows based program. Results : Total number of type 2 diabetic patients with malignancy was 80. Among them 49 (61.3%) were male and 31 (37.7%) were female patients. Almost two-third of the patients was between 41-60 years (63.8%). More than half of the patients belonged to urban settings (42, 52.5%) followed by sub-urban area (27, 33.7%). Smoking was the commonest (23.8%) among the risk factors. Family history for malignancy and exposure to occupational hazards were present in 11.3% and 7.5% cases respectively. Among co-morbid conditions, hypertension and ischemic heart disease were predominant. Twenty categories of malignancies were confirmed by histopathological evidence, radiology reports and cancer markers. The commonest malignancy in male and female was lymphoma and carcinoma breast respectively. Most patients were treated with chemotherapy (48.8%) and combined approach was required in 36.3% cases. Good response to treatment was observed in 46.3% cases, 15% patients deteriorated and death occurred in 6.3% cases. Conclusion : Type 2 diabetes and malignancy individually have their own consequences. When co-existing, patients require a holistic approach. Complications can arise from either spectrum of the diseases. If managed promptly and adequately, outcome of such cases is encouraging. Management outcome of these cases so far in Internal Medicine Department, BIRDEM General Hospital shows a promising future. Bangladesh J Medicine Jul 2017; 28(2) : 70-74